(untitled) (International relations and international law Journal, 2018)
The concept of development in post-industrial society is consolidated to priority of investments into the human capital and increase its his quality, including quality of life, to competitiveness growth of innovative economy. In post-industrial society main «means of production» is qualification of employees and the value of employees for the company sharply increases. As a result the relations between the company and intellectual workers become more partner and the dependence of the employer decreases. Characteristic features of industrial economy are, on the one hand, reproducibility of all factors of production, and with another – proportionality of expenses and results. In industrial society the increase in materials expenses, means of production and labors embodied, as a rule, in the proportional growth of quantity of the let-out benefits. Therefore industrial modernization in all its forms is connected with use of additional resources and labor and it is modernization of mobilization type. Key words: post-industrial economy, investments into the human capital, intellectual work, «society of professionals».